Effect of Data Quality and Task Technology Fit on SIHA Performance in West Papua Province - Wake, Tresia; I. Inan, Dedi; Juita, Ratna; Indra, Muhamad (Universitas Multimedia Nusantara, 2025)
Human Immunodeficiency Virus (HIV) infection remains a global health challenge, including in Indonesia. Effective monitoring is crucial to controlling the spread of this disease, especially in regions like West Papua, which face geographical challenges. Although the HIV/AIDS Information System (SIHA) has been in use since 2012, data quality limitations still affect monitoring effectiveness. Research on the impact of data quality on monitoring performance using the Task Technology Fit (TTF) approach in West Papua remains limited. This study aims to analyze the influence of data quality in SIHA on the effectiveness of HIV/AIDS monitoring through the TTF model. A quantitative method was employed through a survey of 103 SIHA users. Data were analyzed using SEM-PLS to examine the relationships between variables. The results indicate that data quality significantly affects task-technology fit (TTF) and monitoring performance, whereas task, technology, and individual characteristics do not have a significant impact. These findings highlight the importance of improving data quality through validation and user training to support more effective HIV/AIDS monitoring in West Papua.